The changing trend of alloimmunization in antenatal females: experience from a tertiary care centre in north-western India - Yadav, Anshika; Joshi, C. S.; Gupta, G. N.; Dubey, Rounak (International Journal of Research in Medical Sciences, 2021)
Background: Haemolytic disease of the foetus and new-born (HDFN) is a major concern during the antenatal period, especially in countries with low human development index (HDI). The guidelines for antenatal screening and management significantly vary from one geographical region to another. Since the introduction of RhIG immunoprophylaxis, the incidence of HDFN caused by alloimmunization to D antigen has markedly reduced, while that caused by other minor blood group antigens has not been addressed significantly and needs to be given due consideration. Methods: The study was carried out to evaluate the incidence of alloimmunization and analyse various factors associated with HDFN in north-western India. A total of 1700 antenatal cases were evaluated over a period of 20 months, antibody screening and identification was performed on their samples and results were analysed. Results: Out of the 1700 cases, 21 were detected to have the presence of an alloantibody with a prevalence of 1.24%. Out of these, 11 were Rh (D) negative while the remaining 10 were Rh (D) positive. The rate for alloimmunization was higher in females who had a history of blood transfusion (1.24%), bad obstetric history (1.24%), and multigravida status (1.24%). Conclusions: Screening all pregnant females for alloimmunization to RBC antigens, irrespective of their Rh status will help in minimizing the incidence of the HDFN. The practice of providing partial phenotype matched blood to the females of the childbearing age group should be encouraged to reduce the overall incidence of alloimmunization and HDFN.